(untitled) (Al-Aasar, 2025)
This research article examines the role of Muslim countries in countering Islamophobia. The term "Islamophobia" is derived from two words, Islam and phobia, with an additional "o" to link the two concepts. Phobia refers to an irrational fear, aversion, or hatred, so Islamophobia signifies an unfounded fear or hatred of Islam, often accompanied by the association of negative stereotypes with the religion. This study begins by exploring various definitions of Islamophobia and subsequently examines numerous incidents of Islamophobic acts across different countries, which reflect a fear of Islam, its values, and Islamic symbols such as mosques and Islamic schools. In the context of these circumstances, Muslim countries have taken a number of suitable actions to preserve their religious identity and put a stop to the wave of Islamophobia. The OIC presented several resolutions in this regard to the United Nations and March 15 is finally celebrated as the International Day against Islamophobia. This article presents the efforts made in this regard by Pakistan, Qatar, Saudi Arabia, UAE, Egypt, Malaysia, Turkey and Indonesia in a concise manner. Islamic countries need to work together to fight against Islamophobia, so that they can present the correct Islamic image to the Westerners as well as maintain their religious identity.